Les jeunes alévis du quartier de Gazi (Istanbul) et les associations de hemşehri : identifications croisées - Hakan Yücel (European Journal of Turkish Studies)
This article aims to explore the impact of the hemşehri identity on the second generation of Alevi youth living in Gazi district of Istanbul. It advances the following hypothesis: the second generation of gecekondu (shanty town) inhabitants consider the district as the basis of their spatial identity. Most of them are committed to left-wing political parties, and not to hometown associations where social control remains strong. In this context, it seems that the impact of hemşehri identity on second-generation youth is related to the ability of the hometown associations to provide activities tailored for young people, as well as the opportunities it provides for their inclusion within their administrative structure.